Sources and subsurface transport of dissolved reactive phosphorus in a semiarid, no‐till catchment with complex topography. Issue 5 (12th July 2020) - Ortega‐Pieck, Aline; Norby, Jessica; Brooks, Erin S.; Strawn, Daniel; Crump, Alex R.; Huggins, David R.
Abstract: The subsurface transport of dissolved reactive phosphorus (DRP) from artificially drained agricultural fields can impair water quality, especially in no‐till fields. The distribution of soil P in the wheat ( Triticum aestivum L.)‐dominated Palouse region in the inland U.S. Pacific Northwest varies greatly due to its steep and complex topography, and a legacy (∼130 yr) of excessive soil erosion and deposition processes. The primary goal of this research was to better understand the magnitude and temporal dynamics of DRP export from an artificial drain line and the variability of subsurface DRP leaching within a long‐term, no‐till field. Dissolved reactive P in drain line effluent was monitored across three water years. Large intact soil cores were extracted at contrasting field locations (toe and top slope positions) to measure DRP leachate concentration and relative P sorption. Drain line DRP concentration was predominantly >0.05 mg L −1 and often exceeded 0.1 mg L −1 during winter and early spring. Mean leachate DRP levels were significantly higher in toe slope cores than in top slope cores (0.11 and 0.02 mg L −1, respectively). Saturated hydraulic conductivity varied widely across cores and was not correlated with leachate DRP concentration. All soil cores exhibited high P sorption potential, even under conditions of preferential flow. These findings suggest that much of the DRP transport in these landscapes is derived from P hotspots located in toe slope positions. Application of soil P fertilizer amounts in variable rates that account for spatial variability in P transport may minimize P enrichment and subsequent leaching in these locations.